Exclusion of Community forest Associations in Decision Making and its Impact on Forest Condition; Case Study of MT. Elgon and Cherangany Ecosystems - Othim, Roxventa; Owuor, Benjamin (Indian Forester, 2017)
Governance of forestry structure through Participatory Forest Management is backed by Forest Act 2005, which is undergoing a review process. It has been shown that adoption of PFM in some forest stations has resulted in improved forest condition. Community Forest Associations (CFAs) form the major governance structure for implementing PFM. The Constitution of Kenya 2010 created a devolved governance structure which created the County Governments to take services closer to the local communities along- side those to be provided by the Central Government. Though it is not exclusively stated, services from the forestry sector are expected to devolve to the County government. The process of devolution has left out communities in decision making and formulation of rules. It is apparent that CFAs, which represent communities, are not being given their rightful place in the process. Because of this exclusion, the participation of CFAs in forest management is likely to be lower than it was before devolution and this may have impact on the way forests are managed. The objective of the study was to look at the level of CFA involvement in PFM implementation through formulation of rules and decision making. The study used International Forestry Resources and Institutions (IFRI) tools and methodology to analyse CFAs’ roles, activities and participation in inclusive governance in the forest sector. The study was conducted in two water towers in Kenya: Mt. Elgon and Cherangany hills where CFAs are involved in managing the catchment areas. Preliminary results showed that where rules were formulated without the participation of local communities, the forests were more degraded than where local communities were involved.